An Optimization Approach For The Computation Of The Minimum Destabilizing Uncertainty Volume - AL-Sunni, Fouad (2020)
In this paper we propose an non-linear optimization based algorithm for the computation of the stability region for uncertain polynomials. Examples are presented in illustration.